2012
DOI: 10.4236/jbnb.2012.33032
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Functionalized Nanoparticles for Pretreatment of Wheat Straw

Abstract: Perfluoroalkylsufonic (PFS) and alkylsufonic (AS) acid-functionalized magnetic nanoparticles were synthesized and characterized, then evaluated for their ability to hydrolyze hemicelluloses. The magnetic core was made of cobalt spinel ferrite and was coated with silica to protect it from oxidation. The silanol groups allowed surface chemical modification of the nanoparticles with the PFS and AS acid functionalities. Thermogravimetric analysis gave a total organic load of 12.6% and 32.5% (w/w) for AS and PFS na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Their results show that after 24-h reaction at lower temperature (80°C), 3.5±0.1% and 1.0±0.2%, of monosaccharides from xylan were obtained from the two catalysts. However, at higher temperature (160°C for 2 h) xylose yields were observed to be 0.3% and 1.2% from PFS and AS catalysts respectively (Wang et al, 2012). In addition, Tan and Lee (2015) reported 0.77 g glucose (glucose yield of 0.77%) in the pre-treatment liquid, when 100 g of macroalgae cellulosic residue was treated using Dowex (TM) Dr-G8 solid acid catalyst.…”
Section: Effect Of Regular and Magnetic Catalytic Pre-treatment On Sumentioning
confidence: 99%
See 1 more Smart Citation
“…Their results show that after 24-h reaction at lower temperature (80°C), 3.5±0.1% and 1.0±0.2%, of monosaccharides from xylan were obtained from the two catalysts. However, at higher temperature (160°C for 2 h) xylose yields were observed to be 0.3% and 1.2% from PFS and AS catalysts respectively (Wang et al, 2012). In addition, Tan and Lee (2015) reported 0.77 g glucose (glucose yield of 0.77%) in the pre-treatment liquid, when 100 g of macroalgae cellulosic residue was treated using Dowex (TM) Dr-G8 solid acid catalyst.…”
Section: Effect Of Regular and Magnetic Catalytic Pre-treatment On Sumentioning
confidence: 99%
“…It appeared that for Triticale hay regular and magnetic A catalysts facilitated solubilisation of carbohydrate ( Figure 1A and B) corresponding to total sugar yields of 48.87±1.42 mg g -1 and 53.37±0.58 mg g -1 respectively. Wang et al (2012) reported the use of perfluoroalkylsulfonic (PFS) and alkylsulfonic (AS) acid-functionalised magnetic nanoparticles for pre-treatment of wheat straw and attempted to solubilise hemicellulose. Their results show that after 24-h reaction at lower temperature (80°C), 3.5±0.1% and 1.0±0.2%, of monosaccharides from xylan were obtained from the two catalysts.…”
Section: Effect Of Regular and Magnetic Catalytic Pre-treatment On Sumentioning
confidence: 99%
“…Acid functionalized silica materials have been used as catalyst of the α-1,4glycosidic bonds in sucrose and starch [15] and β-1,4glycosidic bonds in cellobiose [16]. Acid functionalized nanoparticles were previously used for the hydrolysis of cellobiose [17] and for the solubilization of hemicelluloses [18]. In this work, silica coated cobalt iron oxide nanoparticles functionalized with propyl-sulfonic acid groups were synthesized and used as catalyst for the pretreatment of corn stover.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been reported on functionalization of nanoparticles for various applications [28] [30]- [32]. In previous work, for instance, magnetic nanoparticles have been successfully coated with silica [33] [34]. These nanoparticles can be separated out of aqueous solutions using a magnetic field, and their silica surface can be further modified.…”
Section: Introductionmentioning
confidence: 99%